Innovative assessment in higher education (Routledge, 2006)
This book is about the difficult process of changing assessment in sometimes unhelpful contexts. The book noffers a unique mix of useful pragmatism and scholarship. Key features include: · case studies illustrating the problems encountered with traditional assessment methods · exploration of the rationales behind different kinds of innovation in assessment · discussion of the complex assessment contexts in which teachers attempt to innovate · contextualization of innovation in assessment within a range of academic settings · theoretical and empirical support forinnovations within higher education